A Prevalence of abomasal worms in sheep in AL-Kut province abattoir: Anas H. H. AL-Dahar and Amer M.A. AL-Amery - AL-Dahar, Anas H. H. (The Iraqi Journal of Veterinary Medicine, 2015)
This study is carried out to determine the prevalence of abomasal nematodes of slaughtered sheep in AL-Kut province from the beginning of October 2013 to the March 2014. A total of 450 abomasum from sheep with different ages and sexes were collected and examined for nematodes detection. The results showed that 311 samples of examined sheep abomasal were infected with Haemonchus contortus. Ostertigia spp. and Parabronema skrjabini and the highest level of prevalence was showed in December (100%) and lowest level was recorded in March (43.47%) and the percentage of infected in young animals (92.35%) compared with adults while the females revealed a high prevalence (75.37%) as compared with males (66.5%). In conclusion, there was a significant effects for the month’s ages and sexes on the prevalence of abomasal nematodes parasites.